3484 Examining the Use of Mobile Technology Among Low-Income African Americans and Hispanics with Hypertension. (27th March 2019) - Kostek, Emily; Cuffee, Yendelela
Abstract : OBJECTIVES/SPECIFIC AIMS: The primary objective of this study was to assess the interest in using mobile technology to manage hypertension and assessing medication adherence among African Americans and Hispanics living in a low-income urban community in Central PA. METHODS/STUDY POPULATION: This qualitative research study was designed using structured interviews with 30 African American participants with hypertension. The study survey consisted of 43 questions which included demographics, use of technology, technology literacy, health literacy, and medication adherence. Participants self-reported their responses about use of technology, literacy, and adherence. The data was examined using summary statistics. RESULTS/ANTICIPATED RESULTS: Out of 30 participants, 61% identified as African American and 30% identified as Hispanic. Overall, participants reported high use of technology; with 63.3% using the internet occasionally, 73.3% having a cell phone, and 66.7% accessing the internet using a mobile handheld device. Participants expressed an interest in measuring blood pressure, accessing health information, and managing medication on their cellphone or tablet. Twenty-five percent of participants self-reported not being confident at all in managing their medication without help and remembering to take their medication as prescribed. Fewer participants (54.2%) were very confident with using technology to help manage medication and treatment. DISCUSSION/SIGNIFICANCE OF IMPACT: This study provides important insights on the use of technology for managing hypertension in an urban low-income community. Results suggest that medication adherence, the use of technology, and the willingness to use mobile applications for hypertension management is high within this low-income community. This study gives future researchers a framework on how to assess these specific areas in their own population.